Dynamic CoRu Bond Shrinkage at Atomically Dispersed Ru Sites for Alkaline Hydrogen Evolution Reaction. Issue 49 (28th October 2021) - Zhang, Hui; Su, Hui; Soldatov, Mikhail A.; Li, Yuanli; Zhao, Xu; Liu, Meihuan; Zhou, Wanlin; Zhang, Xiuxiu; Sun, Xuan; Xu, Yanzhi; Yao, Peng; Wei, Shiqiang; et al.
Abstract: Accurately manipulating the electronic structure of metal active sites under working conditions is central to developing efficient and stable electrocatalysts in industrial water‐alkali electrolyzers. However, the lack of an intuitive means to capture the evolution of metal sites during the reaction state inhibits the manipulation of its electronic structure. Here, atomically dispersed Ru single‐sites on cobalt nanoparticles confined onto macro‐microporous frameworks (M‐Co NPs@Ru SAs/NC) with tunable electron coupling effect for efficient catalysis of alkaline hydrogen evolution reaction (HER) are constructed. Using operando X‐ray absorption and infrared spectroscopies, a dynamic CoRu bond shrinkage with strong electron coupling effect under working conditions is identified, which significantly promotes the adsorption of water molecules and then accelerates its dissociation to form the key H* over Ru sites for high HER activity. The well‐designed M‐Co NPs@Ru SAs/NC delivers efficient HER performance with a small overpotential of 34 mV at 10 mA cm −2 and a high turnover frequency of ≈4284 H2 h −1 at −0.05 V, 40 times higher than that of the benchmark Pt/C. This work provides a new point of view to manipulate the electronic structure of the metal active sites for highly effective electrocatalysis processes. Abstract : Atomically‐dispersed Ru coupled on cobalt nanoparticles within macro‐micro porous nitrogen‐doped carbon are prepared by a carbonization and galvanic replacement strategy. The electronic structure of Ru sites can be accurately manipulated by the dynamic CoRu bond shrinkage under working conditions, which significantly promotes the adsorption and dissociation of the water to form the key H* over Ru sites.